The Wizard Apprentice: A Serious Games System in Immersive VR as a Feasible Rehabilitation Approach in Children With Cerebral Palsy - Cristian Camardella; Federica Serra; Caterina Linciano; Chiara Malasoma; Gabriele Carrieri; Sara Aliboni; Ilaria Bortone; Federico Posteraro; Luca Bonfiglio; Daniele Leonardis (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Virtual reality offers the opportunity to engage the participant in challenging rehabilitation exercises, proposed in the shape of serious games. Modern VR technologies can further enhance usability, allowing the participant to seamlessly interact with VR environment with bare hands, without need of external tracking systems and complex setups. In children neurorheabilitation engagement can promote motivation and attention to the exercise, two key elements for effectiveness of the rehabilitation process. In this work we developed a rehabilitation system composed of three serious games in immersive VR, with motor exercises targeting the upper limb and trunk in children with Cerebral Palsy. The participant plays in the role of a wizard apprentice, called to cast spells, to prepare potions and to ride a magic eagle. These game scenarios involve coordinated motor functions related to trajectory tracking, pick-and-place with prono-supination, and trunk balance. The presented pilot study (12 CP children, 24 sessions), focuses on the feasibility assessment of the rehabilitation method, then, it allows a more in depth analysis on the adaptation and progress of the exercise parameters through data recorded during the whole treatment. The study shows that immersive VR games are a feasible approach in rehabilitation procedures, with positive results regarding acceptability, retention, adherence to the planned exercises and absence of adverse effects in the long-term use. They also show promising results in improvements of motor functions, although a direct comparison with a control group was not included in the study.